2006
DOI: 10.1007/s10815-006-9070-0
|View full text |Cite
|
Sign up to set email alerts
|

Donation of surplus frozen embryos for stem cell research or fertility treatment—Should medical professionals and healthcare institutions be allowed to exercise undue influence on the informed decision of their former patients?

Abstract: The increasing availability of clinical assisted reproduction has led to an accumulated surplus of frozen embryos within fertility clinics worldwide. Couples that have attained success in clinical assisted reproduction, and have no further desire to reproduce; are often faced with an agonizing dilemma on what to do with their surplus frozen embryos-whether to simply discard them, or donate either for scientific research or to other infertile couples. There is a risk that persons or institutions directly involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
14
1
1
Order By: Relevance
“…It has also been shown that in addition to how patients (recipients and IVF patients) conceptualize their embryos (tissue vs. child), perceptions of the medical team play a role in their decision-making process [ 38,39 ] . The more comfortable patients are with the medical team, the more apt they are to donate their embryos for scienti fi c studies.…”
Section: To Whom Do Recipients Donate Their Embryos?mentioning
confidence: 99%
“…It has also been shown that in addition to how patients (recipients and IVF patients) conceptualize their embryos (tissue vs. child), perceptions of the medical team play a role in their decision-making process [ 38,39 ] . The more comfortable patients are with the medical team, the more apt they are to donate their embryos for scienti fi c studies.…”
Section: To Whom Do Recipients Donate Their Embryos?mentioning
confidence: 99%
“…Physical risks include (a) those associated with ovarian stimulation, including ovarian hyperstimulation syndrome, abdominal pain, fatigue, mood changes, strokes, renal failure, heart attacks and possibly ovarian or uterine cancer and (b) those associated with the surgical retrieval of ova such as bleeding and hemorrhage, pelvic injury, and infection [24,48]. The social risks to women ova providers include exploitation and undue influence due to substantive compensation (financial or other) [3] and gratitude for services towards physicians [34], both of which may undermine the ability of some women to provide voluntary informed consent. A marginalized population of women may fall victims to such exploitation, especially in nations where the provisions on research ethics are less stringent and where poverty is more pronounced [20,67].…”
Section: Destruction Of Embryos and Harms To Womenmentioning
confidence: 99%
“…It must be noted that even if embryo commercialization is prohibited and no profit is allowed to be made directly from the transaction of frozen embryos between donor and recipient, there is still much opportunity for profit-making in medical fees arising from laboratory and clinical services rendered to the recipient (Heng, 2006). In fact, it is possible that the 'sale' of donated embryos may be 'disguised' as substantially increased medical fees, at a premium above that billed to other patients for utilizing their own embryos in a self-freeze -thaw embryo transfer cycle.…”
Section: Independent Counselling On Embryo Donation For Infertility Pmentioning
confidence: 99%
“…Very often, formerly infertile couples who have attained reproductive success feel an overwhelming sense of gratitude to the fertility doctor who previously oversaw their treatment. Hence, there is a risk of medical professionals exploiting the doctor -patient fiduciary relationship (based ultimately on goodwill and trust) to exercise undue influence on their former patient's decision to either terminate or donate their surplus frozen embryos (Heng, 2006).…”
Section: Independent Counselling On Embryo Donation For Infertility Pmentioning
confidence: 99%
See 1 more Smart Citation